THE ROLE OF LEARNING VOCABULARY IN ENGLISH FOR SPECIFIC PURPOSES - Акмырадов, Гадам Гаммарович; Гельдыева, Бахар Джуманазаровна (Перспективные направления инновационного развития и подготовки кадров, 2024)
In the contemporary world, proficiency in English has become a vital asset across various domains. The role of English for Specific Purposes (ESP) has gained prominence in higher education, where students are required to attain language skills tailored to their particular fields of study or professional aspirations. ESP serves as a bridge that connects learners with the language demands of their disciplines, making vocabulary development a crucial component of this educational approach. A well-developed vocabulary not only enhances communication but also deepens comprehension, allowing students to express their ideas with precision and confidence. The article explores the lexical approach in ESP and its significance in vocabulary teaching, the types of vocabulary, including technical and semi-technical terms, as well as the Academic Word List (AWL). It also discusses different vocabulary learning strategies and technology, which enhanced vocabulary for ESP students.